2021
DOI: 10.31413/nativa.v9i5.13079
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores Qualitativos Do Ambiente Edáfico E Serviços Ecossistêmicos Em Diferentes Sistemas De Ocupação Da Terra

Abstract: O conceito de sustentabilidade tem levado a pesquisa agropecuária a uma crescente busca de modelos alternativos e sustentáveis para a agricultura, sendo as formas de uso e manejo do solo o ponto de partida determinante para a compreensão da dinâmica do ambiente edáfico e serviços ambientais dos agroecossistemas. Sendo assim, este trabalho teve como objetivo avaliar a qualidade do ambiente edáfico e serviços ecossitêmicos em diferentes sistemas de ocupação da terra, através de indicadores ambientais qualitativo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Silva et al (2022) found that areas with natural vegetation present approximately 28% lower soil temperature when compared to areas with little plant cover, and that environmental stimuli, such as temperature and soil moisture, affect the organic matter decomposition dynamics and, consequently, the release of soil CO 2 , indicating that management techniques that reduce the soil surface temperature and increase organic matter contents should be prioritized to improve soil biota. These attributes emerge as important indicators of soil environmental quality, as they estimate the extent of functional sustainability regarding ecological aspects of land use and occupation systems (SILVA et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al (2022) found that areas with natural vegetation present approximately 28% lower soil temperature when compared to areas with little plant cover, and that environmental stimuli, such as temperature and soil moisture, affect the organic matter decomposition dynamics and, consequently, the release of soil CO 2 , indicating that management techniques that reduce the soil surface temperature and increase organic matter contents should be prioritized to improve soil biota. These attributes emerge as important indicators of soil environmental quality, as they estimate the extent of functional sustainability regarding ecological aspects of land use and occupation systems (SILVA et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The present findings provide crucial information for research on the management and conservation of tropical soils and may allow us to infer that the forms of land use and occupation induce changes in the quality of the soil environment, which may have repercussions on the establishment of populations or communities and their processes (J. H. C. S. Silva et al, 2021). This knowledge can stimulate the use of management techniques to support the recovery of modified areas and the insertion of more sustainable production systems, aiming at mitigating global warming.…”
Section: Mandalamentioning
confidence: 91%
“…The increasing soil degradation has promoted the adoption of agricultural management techniques that combine agricultural production with conservation of the soil environment (J. H. C. S. Silva et al, 2021). In this respect, systems that integrate natural vegetation and ecosystems transformed by humans are efficient for the production of goods and services, besides acting as a potential carbon sink for the atmosphere by storing a greater amount of carbon in the soil (Nogueira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Longo, Espindola e Ribeiro (1999) ao se considerar a atenuação devido às modificações antrópicas no meio, deve-se observar a estreita relação entre o solo e a vegetação (Costa et al, 2020). Além disso, deve-se utilizar-se de indicadores de qualidade, seja do solo ou da própria vegetação, a fim de se avaliar os mecanismos formados a partir da implantação desses sistemas de recuperação (Silva et al, 2020;Silva et al, 2021, Araujo et al, 2019 Objetivou-se com este trabalho quantificar os nutrientes no solo sob duas espécies de leguminosas (M. velloziana e T. candida) e em área com Floresta de Tabuleiros, e estimar o balanço de nutrientes no sistema solo-planta na área com as leguminosas.…”
Section: Introductionunclassified